Exploring the significant predictors of convergent and divergent scientific creativities. (March 2019) - Yang, Kuay-Keng; Hong, Zuway-R.; Lee, Ling; Lin, Huann-Shyang
Highlights: Little existing research investigated multiple path estimate of scientific creativity. There is synergistic effect of creativity learning environment and domain-specific knowledge on scientific creativity. Science inquiry plays a critical role on convergent scientific creativity. Abstract: Despite that the importance of scientific creativity has been emphasized in literature, limited attention has been paid to the identification of multiple path estimates of scientific creativity. This two-stage study investigated significant predictors and pathway effects of divergent and convergent scientific creativities. Stage one was focused on the development and validation of instruments. At stage two, convenience samples of 307 elementary students from four different schools were asked to respond to the creativity learning environment questionnaire, scientific creativity test, and science inquiry test. The results of structured equation modeling analyses supported that there is a synergistic effect of creativity learning environment and performance of science achievement on student performance of science inquiry and scientific creativity. In addition, this study identified that creativity learning environment and performance of science achievement are significant predictors of divergent scientific creativity while science inquiry plays a critical role on student convergent scientific creativity.